Longitudinal Characterization of Motor and Cognitive Deficits in a Model of Penetrating Ballistic-Like Brain Injury - Shear, Deborah A.; Lu, Xi-Chun May; Bombard, Matthew C.; Pedersen, Rebecca; Chen, Zhiyong; Davis, Angela; Tortella, Frank C. (Journal of neurotrauma, 2010)
Traumatic brain injury (TBI) produces a wide range of motor and cognitive changes. While some neurological symptoms may respond to therapeutic intervention during the initial recovery period, others may persist for many years after the initial insult, and often have a devastating impact on quality of life for the TBI victim. The aim of the current study was to develop neurobehavioral testing parameters designed to provide a longitudinal assessment of neurofunctional deficits in a rodent model of penetrating ballistic-like brain injury (PBBI). We report here a series of experiments in which unilateral frontal PBBI was induced in rats, and motor/cognitive abilities were assessed using a battery of tests ranging from 30 min to 10 weeks post-injury. The results showed that PBBI produced consistent and significant (1) neurological deficits (neuroscore examination: 30 min to 10 weeks post-PBBI), (2) sensorimotor dysfunction in the contralateral forelimb (forelimb asymmetry task: 7 and 21 days), (3) motor dysfunction (balance beam task: 3-7 days; and fixed-speed rotarod task: 3-28 days), and (4) spatial learning deficits in the Morris water maze (MWM) task out to 10 weeks post-injury. Overall, the results of this study demonstrate that PBBI produces enduring motor and cognitive deficits, and identifies the optimal task and testing parameters for facilitating longitudinal screening of promising therapeutic interventions in this brain injury model.